1997
DOI: 10.1007/s001250050663
|View full text |Cite
|
Sign up to set email alerts
|

b 3 -adrenergic-receptor polymorphism: a genetic marker for visceral fat obesity and the insulin resistance syndrome

Abstract: Obesity is a complex phenotype resulting from the combined effects of genes, behavioural and lifestyle factors, and their interactions [1]. The associations between obesity and increased risk of morbidity and mortality are well documented [2]; however, distribution of body fat is also of importance [3]. A syndrome with a clustering of multiple risk factors for coronary atherosclerosis has been described and defined by Reaven [4] as syndrome X; by Kaplan [5] as the deadly quartet; and by Matsuzawa et al. [6]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
56
4
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(71 citation statements)
references
References 26 publications
10
56
4
1
Order By: Relevance
“…However, the lipid levels were similar in the two obese groups. Our results are in concert with the findings of Strazullo et al (2001) and Sakane et al (1997). We are aware of the weaknesses of the present study, which are as follows: (1) confounding factors, such as socioeconomical background, physical activity and nutrition, which could also play a role in the differences found in the present study, were not investigated; (2) other polymorphisms (eg uncoupling protein 1, 2 and 3 and peroxisome proliferator-activated receptor-gamma genes) that were not studied in the present sample may also interact.…”
Section: Discussionsupporting
confidence: 92%
“…However, the lipid levels were similar in the two obese groups. Our results are in concert with the findings of Strazullo et al (2001) and Sakane et al (1997). We are aware of the weaknesses of the present study, which are as follows: (1) confounding factors, such as socioeconomical background, physical activity and nutrition, which could also play a role in the differences found in the present study, were not investigated; (2) other polymorphisms (eg uncoupling protein 1, 2 and 3 and peroxisome proliferator-activated receptor-gamma genes) that were not studied in the present sample may also interact.…”
Section: Discussionsupporting
confidence: 92%
“…11,[37][38][39] The high expression and activity of ADRB3 in visceral adipose tissue is consistent with our observed association between the ADRB3 variant and visceral, but not subcutaneous fat. Findings from a previous study of Japanese women 40 also indicated a significant association between the ADRB3 Trp64Arg substitution and visceral abdominal fat. In our African-American cases, the positive association between ADRB3 and obesity was found for the wild-type receptor, and in Japanese women, the association was found for the variant.…”
Section: Adrb3 and Obesity R Mckean-cowdin Et Almentioning
confidence: 70%
“…1 Other studies have found the R allele is not associated with BMI, fat distribution, metabolic variables, visceral fat cell size and lipolytic response to noradrenaline, in normal weight or obese non-diabetic individuals. 15 However, a number of Japanese studies have shown an association of the mutant allele with BMI, 13,16,17 with visceral fat, 18 and with a blunted response to treatment of obesity in women. 19 The high frequency of the W64R mutation reported in nonobese Japanese subjects, 17 together with uniform allele frequency with respect to BMI within ethnic groups suggests that the mutation itself is not a major determinant of obesity.…”
Section: Discussionmentioning
confidence: 99%